2020
DOI: 10.1155/2020/8875987
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome in Children (MIS-C) Associated with 2019 Novel Coronavirus (SARS-CoV-2) Infection

Abstract: We report three critically ill pediatric patients (aged 6–10 years), presenting with features of multisystem inflammatory syndrome in children (MIS-C) from April 4 to May 10, 2020, to a tertiary-care center in New Jersey, United States. All patients tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and were previously healthy. Clinical presentations were similar with fever, abdominal pain, gastrointestinal complaints, and/or rash. One patient had altered mental status w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 5 publications
7
65
0
1
Order By: Relevance
“…Predominant symptoms of stomach and prevalence of cholestasis than the liver injury hypothetically caused by the higher expression of angiotensin-converting enzyme-2 receptors in the gastrointestinal epithelium cells and cholangiocytes than in hepatocytes [ 9 ]. Our patients had circulatory shock requiring subsequence inotropic support, similar to the study of MIS-C by Kest et al in New Jersey, United States of America/USA [ 10 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Predominant symptoms of stomach and prevalence of cholestasis than the liver injury hypothetically caused by the higher expression of angiotensin-converting enzyme-2 receptors in the gastrointestinal epithelium cells and cholangiocytes than in hepatocytes [ 9 ]. Our patients had circulatory shock requiring subsequence inotropic support, similar to the study of MIS-C by Kest et al in New Jersey, United States of America/USA [ 10 ].…”
Section: Discussionsupporting
confidence: 72%
“…Feldstein et al reported their study of MIS-C in the United States, there is only 70 % that PCR was positive [ 8 ]. Leukocytosis was found, this is following the research by Kest et al, which in his research all patients with MIS-C was leukocytosis [ 10 ]. Our case had severe anemia and leukocytosis, but lymphocytopenia was not found.…”
Section: Discussionsupporting
confidence: 57%
“…CSF pleocytosis may be indicative of infection, inflammation or other CNS injury [ 247 ]. There were 29/409 patients (7%) who had a CSF WBC count of 21–100 cells/μL, all of whom had symptoms that localized to the CNS; 10 (34%) of these patients had CSF RBC counts provided, all of whom had a CSF RBC count of <300 cells/μL; Naz et al described a patient with headache and indicated that CSF was consistent with viral meningitis, but the CSF WBC count was unclear, as it was noted that he had 90 lymphocytes and 10 neutrophils (no units provided so we were unsure if these were percentages or numbers of cells), so we classified these findings as “increased WBC.” [ 10 , [27] , [28] , [29] , 44 , 75 , 79 , [127] , [128] , [129] , 140 , 145 , 154 , 160 , 161 , 170 , 173 , 183 , 184 , 187 , 198 , 205 , 208 , 216 ]
Fig. 3 Cerebrospinal fluid white blood cell count results.
…”
Section: Resultsmentioning
confidence: 99%
“… N.A. MIS-C, shock IVIg, ASA Recovered [ 232 ] 1 (confirmed) F 10y MIS-C, shock None Recovered [ 233 ] 1 (confirmed) F 5y MIS-C, shock IVIg, ASA Recovered [ 234 ] 3 (all confirmed) 1 M 2 F 8.3y MIS-C, shock 2 IVIg, 3 glucocorticoids, 1 TCZ Recovered [ 235 ] 10 (8 confirmed) 10 M 6 F 9.2y MIS-C, 10 shock 5 IVIg, 10 glucocorticoids, 2 anakinra Recovered 4 Coronary artery abnormalities [ 236 ] 6 (all confirmed) 2 M 4 F 6y MIS-C, 5 shock 6 IVIg, 6 glucocorticoids Recovered [ 237 ] 12 (all confirmed) 9 M 3 F 8y MIS-C N.A. Recovered 2 Coronary artery abnormalities [ 238 ] 15 (all confirmed) 9 M 6 F 11.5y MIS-C 12 IVIg, 3 glucocorticoids, 9 TCZ, 2 anakinra, 2 ASA 1 Death …”
Section: Resultsmentioning
confidence: 99%